Clinical Assessment of Malnutrition in Patients With Gastrointestinal Cancer During Chemotherapy: A Prospective Study - Moghimi, Minoosh; Eghdam ZamiriR, Reza; Salarpour, Fatemeh; Ghadimi, Zahra; Baba Ali, Sahar; Nazaraian, Morteza; Jafari, Sattar; Hashemi Nejad, Leili; Salimi, Maryam; Abbaspour, Zahra; et al. (Reports of Radiotherapy and Oncology, 2015)
Background: Malnutrition is common in patients with cancer and in many cases can result in shortened survival rate. More than 20% of cancer mortality can be attributed to the effects of malnutrition, rather than malignancy itself. Malnutrition results in poor response to treatment, increased length of hospital stay, immunodeficiency, reduced quality of life, and increased health care costs in patients with cancer. Objectives: The aim of this study was to assess the nutritional status of patients with gastrointestinal cancer during chemotherapy. Patients and Methods: In this study, 92 patients over the age of 18 who were referred to Valie-e-Asr hospital of Zanjan (since Apr, 2011 to Dec, 2011) were selected. Nutritional status of patients during 3 cycles of chemotherapy was assessed by a questionnaire. The obtained data were statistically analyzed by ANOVA, using SPSS 16.0. Results: There was a significant relationship between duration of treatment and the average of mid arm circumference (MAC) and body mass index (BMI). BMI can be considered as an anthropometric index which can be used to alarm the physicians about nutrition problems of the patient. Conclusions: At the end of treatment, patients who survived had better nutritional statuses compared to the ones who passed away. During chemotherapy, malnutrition got worse in patients with metastatic esophageal cancer. Our findings show that patients with moderate or severe malnutrition are in the critical need to improve their malnutrition status.